PEDAGOGICAL CONDITIONS FOR THE DEVELOPMENT OF PROFESSIONAL COMPETENCE OF FUTURE EMPLOYEES OF INTERNAL AFFAIRS BODIES (Scientific journal of the Fergana State University, 2024)
This article describes the content of the professional competence of future internal affairs officers, the forms and methods of its development, the qualities of professional competence and their essence. Also, the issues of development of professional competence in the system of educational institutions of the internal affairs bodies are highlighted.